Ectoparasitic mites and their Drosophila hosts. Issue 1 (2nd January 2017) - Perez-Leanos, Alejandra; Loustalot-Laclette, Mariana Ramirez; Nazario-Yepiz, Nestor; Markow, Therese Ann
ABSTRACT: Only two parasite interactions are known for Drosophila to date: Allantonematid nematodes associated with mycophagous Drosophilids and the ectoparasitic mite Macrocheles subbadius with the Sonoran Desert endemic Drosophila nigrospiracula . Unlike the nematode- Drosophila association, breadth of mite parasitism on Drosophila species is unknown. As M. subbadius is a generalist, parasitism of additional Drosophilids is expected. We determined the extent and distribution of mite parasitism in nature Drosophilids collected in Mexico and southern California. Thirteen additional species of Drosophilids were infested. Interestingly, 10 belong to the repleta species group of the subgenus Drosophila, despite the fact that the majority of flies collected were of the subgenus Sophophora. In all cases but 2, the associated mites were M. subbadius. Drosophila hexastigma was found to have not only M. subbadius, but another Mesostigmatid mite, Paragarmania bakeri, as well. One D. hydei was also found to have a mite from genus Lasioseius attached. In both choice and no-choice experiments, mites were more attracted to repleta group species than to Sophophoran. The extent of mite parasitism clearly is much broader than previously reported and suggests a host bias mediated either by mite preference and/or some mechanism of resistance in particular Drosophilid lineages.